Penguatan Karakter Antikorupsi dalam Meningkatkan Kompetensi Kewarganegaraan Peserta Didik - Pramudyasari Nur Bintari; Dwi Endah Kurniasari; Weli Agus Setiawan; Yollanda Octavitri (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study aims to analyze the implementation of anti-corruption education in enhancing the civic competence of cadet students at the Banten Maritime Polytechnic. Anti-corruption education is considered essential in shaping character, integrity, and professional ethics of cadets as future seafarers and responsible citizens. The study employs a descriptive qualitative approach supported by simple quantitative data. Data were collected through observation, interviews, documentation, and literature review involving Diploma III cadets enrolled in Pancasila Education and Citizenship Education courses. The findings indicate that cadets’ perceptions of anti-corruption education are positive, as reflected in their understanding of values such as honesty, responsibility, discipline, and social awareness. The implementation of anti-corruption education is carried out through curriculum integration and the reinforcement of e-learning on Basic Anti-Corruption Knowledge and Integrity via the KPK platform. Out of 197 cadets, 58% successfully completed the e-learning within a maximum period of one semester. These findings demonstrate an improvement in civic competence, particularly in the knowledge dimension, and support the strengthening of anti-corruption character through learning processes and a sustainable cadet mentoring system that aligns with the demands of national maritime vocational education.